2020
DOI: 10.32615/ps.2019.146
|View full text |Cite
|
Sign up to set email alerts
|

Special issue in honour of Prof. Reto J. Strasser - Chlorophyll a fluorescence of Bertholletia excelsa Bonpl. plantations under thinning, liming, and phosphorus fertilization

Abstract: Phosphorus (P) fertilization and liming can reduce negative effects caused by a sudden increase in light availability after thinning of forest plantations. In this study, immediately after thinning, photochemical performance (quantum yield of PSII and performance index) decreased, however, liming and P fertilization reduced the negative effects caused by thinning and accelerated the recovery of Bertholletia excelsa trees. After thinning, the remaining trees increased J-I phase with the formation of a positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
1
17
1
Order By: Relevance
“…Miscanthus species (44,45). Positive correlations were previously found among Fe, the performance index and electron transport (46) and between electron transport and photosynthesis (47,48). In contrast, no correlation was observed between photosynthesis and ChF variables in barley plants under drought and control treatments (12).…”
mentioning
confidence: 86%
“…Miscanthus species (44,45). Positive correlations were previously found among Fe, the performance index and electron transport (46) and between electron transport and photosynthesis (47,48). In contrast, no correlation was observed between photosynthesis and ChF variables in barley plants under drought and control treatments (12).…”
mentioning
confidence: 86%
“…A few studies have evaluated the combined effects of seasonality and fertilization on chlorophyll fluorescence. A recent study with Brazil nut trees (Bertholletia), an adapted species to nutrient-poor soils, showed ChF adjustments to light environments when thinned and fertilized with phosphate [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the combined effects of fertilization and seasonality on ChF traits in tropical tree legumes are also lacking. Studies have demonstrated the correlations between ChF variables and growth, photosynthesis and nutrient traits in Bertholletia and crop species [26,[32][33][34]. Therefore, three main hypotheses were tested: 1.…”
Section: Introductionmentioning
confidence: 99%
“…As the light supply can be very heterogeneous, the plants, more specifically their leaves, must exhibit great flexibility of physiological responses to cope with light fluctuations. Given the spatial and seasonal changes in the availability of primary resources, plants with low physiological flexibility would likely be constrained in their ability to survive in changing environments [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in conditions where light is limiting, the increase of nutrient concentrations in leaves plays a major role in the use of light energy. This is due to the requirements for N, P, and micronutrients for the synthesis of the photosynthetic apparatus [ 2 , 16 ]. On the other hand, it is believed that, in plants subjected to high irradiance, an adequate mineral nutrition can improve the defense mechanisms against high light stress [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%